Maarwah Tradition In Banjar Society: Correlation And Problems Of The Maarwah Tradition (One Hundred Days) Of Husband As The Limit Of Wife's Iddah - Pratama, Akhmad Dzika; Hayati, Fauzia; Ramadani, Muhammad Faqih (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
Iddah is the waiting period for a woman who has been divorced or whose husband has passed away. The Banjarese people often associate iddah with maarwah, a traditional death commemoration ritual. They believe that a woman whose husband has died is not allowed to remarry before the manyaratus (one hundred days after death) period is completed. This study analyzes the intersection between the concept of iddah and the maarwah tradition, highlighting their correlation and the legal-socio-cultural issues that arise from the belief that a widow cannot remarry until one hundred days after her husband’s death. This research employs a normative library research method using Islamic jurisprudence theory as the analytical tool. The findings show that iddah and maarwah are correlated through shared values of ethics and etiquette, serving as an expression of a wife's love and respect for her deceased husband. However, the belief that a woman cannot remarry before completing the manyaratus should not be interpreted merely textually but understood in light of its deeper cultural and moral significance.